Social Welfare of Alternative Controlled-Price Policies - Buccola, Steven T.; Sukume, Chrispen (The Review of Economics and Statistics, 1993)
Recent developments in social welfare analysis provide insights into the selection of price policies. In the presen t paper a CES social welfare function and a weighted average of utilitarian and leximin rules are used to identify optimal producer prices in an economy where government is the price setter and agents are risk averse. The analysis distinguishes between the interests of commercial producers, peasant producers, consumers, and taxpayers. A n application to Zimbabwe indicates that a maize producer price in the low-medium to medium portion of the historical range would be social ly optimal if egalitarian preferences are moderate. This outcome is somewhat insensitive to group weighting schemes and to interpersonal utility correspondences. Copyright 1993 by MIT Press.